الإحالة بالروابط اللفظية وأثرها في تماسك النص: خطبة الوسيلة (أنموذجا) - المحنه علي شاكر جواد (Al-Adab Journal, 2019)
The basic function of textual linguistics was to show the coherence between linguistic text units, to reveal grammatical relations, semantic correlations, conjunctive, indicative, and other relationships of the sentence level, on the one hand, and beyond the level of sentence on the other ؛Therefore, this research aims primarily to study the impact of referral in the cohesion and interdependence of the text. We have chosen for this a sermon from the speeches of the Commander of the Faithful Ali bin Abi Talib (peace be upon him) called the sermon (the means) of the study to reveal what literary text and literary art Linguistic and objective. This is done with several tools, including referral. It is one of the important means of cohesion of the text, because it works to strengthen the links between the parts of the text and make them more coherent and cohesive and the researcher’s study in the study of referral in the text two methods: the first: the reference pronouns and names linked and the names of the reference .